African Forum for Research in health (AFREhealth) student exchange pilot: an impact assessment - Faith Nawagi, MIPH; Anna M Iacone, MSc; Danielle Tinder, MSc; Justin Seeling, MSc; Eunice Kamami, BSc; Amanda Sit, BSc (Elsevier, 2019)
Background: For many medical and allied health students from African countries, the opportunity to undertake a global health elective abroad is unaffordable or inaccessible. Therefore, an imbalance has emerged where many African institutions host students from developed countries but their own students rarely go on electives in developed countries. Global Educational Exchange in the Medical and Health professions (GEMx), a service programme of the Educational Commission for Foreign Medical Graduates (ECFMG) partnered with the African Forum for Research in Health (AFREhealth) to implement a south-to-south student exchange pilot through intra-institutional partnerships. The aim was to provide affordable global-health learning opportunities to African students. Methods: 13 medical and nursing institutions in eight African countries participated in the AFREhealth pilot. Institutions entered into a multilateral agreement. The GEMx web-based system was used to centralise elective placements where students gained access to opportunities and applied online. Host institutions waived their administrative fees and provided a manager to support incoming students. ECFMG hired a contractor to do partnership development and work with students and leaders at participating institutions. ECFMG GEMx provided student mini-grants to cover travel, accommodation, and living expenses. We used SurveyMonkey to collect feedback from students, institutions, and AFREhealth leadership and to run descriptive analysis. Findings: Between April, 2017, and June, 2018, GEMx facilitated 48 student exchanges in medicine, nursing, and pharmacy in Ghana, Kenya, Malawi, South Africa, Tanzania, Uganda, Zambia, and Zimbabwe. 20 students (42%) reported that they had not previously gone on an elective exchange in another country and that this opportunity would not have been possible without GEMx. The most common learning experiences reported by institutions were that students: learned about and compared different health systems; improved clinical skills and gained knowledge that is applicable back home; increased confidence; developed professional networks; and managed and cared for patients who differed from those in their previous educational experience. These findings correlated with feedback collected from students. Interpretation: Translation and implementation for impact in global health requires models that provide opportunities for global exposure to various health-care settings. With little global exposure for African medical and allied health professional training students, the south-to-south model provides a suitable and cost-effective platform to address the gap. Outcomes from the pilot showed a strong commitment from intra-institutional partners within AFREhealth to the south-to-south model. Although ECFMG GEMx funding made student exchanges possible for the AFREhealth student exchange pilot, additional funding contributions are needed to expand the south-to-south student exchange programme. Funding: ECFMG Challenge Grant.